Implementation of a practical sand constitutive model coupled with the high cycle accumulation framework in PLAXIS - Pishun Tantivangphaisal; David M.G. Taborda; Stavroula Kontoe (MethodsX, 2025)
A modification of the high-cycle accumulation (HCA) framework coupled with a practical constitutive model for sands and its numerical implementation as a user-defined soil model in PLAXIS is presented. The implemented model is compared against data from the original high-cyclic tests in Karlsruhe fine sand and more recent laboratory tests in Dunkirk sand. A reference 15 MW offshore wind turbine monopile foundation subject to lateral cyclic wave loading is used in an engineering design scenario at three different load levels to verify the current numerical implementation.Details include: • Modifications made to the HCA framework to couple it with a practical sand constitutive model, • Implementation of an efficient workflow to switch between low and high cycle constitutive equations in PLAXIS, and • Verification of the implementation at single element and boundary value problem scales.